Text Mining Of Sharia Economic Law Disputes In Religious Courts - Farhan Muhammad Ikhsan; Fahmi Ali Hudaefi (proceedings.icesy, 2026)
The practice of resolving Islamic economic disputes in the Religious Court shows an increasing trend in line with the increasingly massive use of Islamic financing contracts in community economic activities. In this context, the murabahah contract has become one of the most frequently used contracts as well as the one that gives rise to the most disputes, especially those related to the implementation of the obligations of the parties and the validity of the contract elements. This condition has created a need for studies that not only examine the normative aspects of murabahah contracts but also identify patterns of disputes that arise in judicial practice. This study aims to analyze Islamic economic disputes in the Religious Court by examining patterns of Islamic contracts and their relationship with the characteristics of the disputes that occur. The research method used is normative legal research with a text mining-based case approach to Religious Court decisions related to murabahah disputes taken from the Indonesian Supreme Court Decision Directory, thus enabling objective and systematic legal data analysis. The findings show that murabahah disputes are dominated by customer default due to failure to meet payment obligations, as well as a lack of understanding among the parties regarding the object of the contract and the determination of the selling price. In addition, although mediation based on the principle of sulhu has been implemented, its effectiveness still faces obstacles in the form of limited understanding of sharia law and inaccurate dispute resolution clauses. The originality of this research lies in the use of text mining methods on Religious Court decision data sourced from the Supreme Court Directory, which is still rarely used in studies of sharia economic disputes in Indonesia, particularly